Alih Kode Dan Campur Kode Dalam Film Komedi Fantas “Penguasa Dunia” - Putri Wahyu Pramudita; Umi Marfiatin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Code-switching and code mixing can not only be found in direct speech but also in social media such as videos on the YouTube platform, one of which can be found on the Lula Studio YouTube video channel entitled "Ruler of the World". The purpose of this research is to discuss the form of code switching and the form of code mixing. The method used in this research is descriptive qualitative method with data collection techniques using listening and note-taking techniques. There are 36 pieces of code-switching and code-mixing data in this study, which are in the form of internal and external code-switching. While in the form of code mix, data was found in the form of word insertion iner code mix, phrase insertion iner code mix, and clause insertion iner code mix. For outer code mix, namely outer code mix of word inserts and phrase inserts.